Burden of hepatocellular carcinoma among hispanics in South Texas: a systematic review - John Ha; Aysha Chaudhri; Abhishek Avirineni; Jen-Jung Pan (BMC, 2017)
Abstract Background Hepatocellular carcinoma (HCC) is one of the fastest rising causes of cancer-related mortality in the United States (U.S.). Despite improved HCC screening and surveillance guidelines, significant race/ethnicity-specific disparities in hepatocellular carcinoma remain, disproportionately affecting at risk racial minorities in the U.S. The current review aims to provide an updated analysis on race/ethnicity-specific disparities in HCC epidemiology with a focus on predisposing risk factors. Conclusion Among different race/ethnicities in the U.S., Hispanics experienced the greatest burden of HCC, particularly those residing in South Texas. It is important to understand that the underlying etiologies for these disparities are complex and multi-factorial. Some of these risk factors for developing chronic liver disease include non-alcoholic fatty liver disease/non-alcoholic steatohepatitis and alcohol use. In addition, population genetics, acculturation of ethnic minorities, and access to healthcare may be further contributing to the observed disparities in HCC. By increasing awareness, improved modalities for screening and surveillance for HCC are important in guiding future research for targeted preventive and therapeutic interventions.